Physics Learning Media Based on Mobile Learning on the Android Platform to Increase Student’s HOTS - Dian Rif'atul A'yun; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2024)
This research was motivated by the need for media for learning physics that can be used anytime and anywhere to improve students' HOTS physics skills, the researchers designed learning media based on mobile learning on the Android platform. This study aims to: develop physics learning media to improve students' physics HOTS skills, designing physics learning media for learning valid, effective and practical students. The research subjects were students of class X MIPA at MAN 3 Sleman. The instruments used are questionnaires and tests. This research uses research and development or what is known as Research and Development (R&D) with the ADDIE development model consisting of 5 (five) stages, namely Analysis, Design, Development, Implementation, and Evaluation. The results of the validity test from material and media experts obtained that physics learning media based on mobile learning on the Android platform was included in the eligibility criteria which were very valid and could be used. The practicality test by students on learning media users found that physics-based mobile learning media on the Android platform were included in very practical criteria. As for the effectiveness test of the product developed, it was found that physics learning media based on mobile learning on the Android platform was effective in improving physics HOTS skills.